Simulation of gas sensing with a triboelectric nanogenerator - Zhao, Kaiqin; Gan, Hua; Li, Huan; Liu, Ziyu; Zhu, Zhiyuan (Beilstein Journal of Nanotechnology, 2021)
Safety concerns require the frequently check for leaks in gas pipelines. Also, in coal mines the type gases permeating from the ground need to be monitored. Triboelectric nanogenerators (TENGs) can be applied for gas sensing without external power supply. In this paper, a two-dimensional model of a TENG was established, and a gas jet a rectangular cross section was added between two triboelectric materials. The TENG could generate distinguishable electrical signals according to the different types of gas and the different gas injection areas. This work contributes to the area of self-powered gas sensing.
Keywords: gas; sensor; triboelectric nanogenerator (TENG)

(untitled) - Xu, S.; Zhang, Y.; Jia, L.; Mathewson, K. E.; Jang, K.-I.; Kim, J.; Fu, H.; Huang, X.; Chava, P.; Wang, R.; Bhole, S.; Wang, L.; et al. (Science, 2014)

(untitled) - Zhang, X.-S.; Han, M.; Kim, B.; Bao, J.-F.; Brugger, J.; Zhang, H. (Nano Energy, 2018)

(untitled) - Li, X.; Lin, Z.-H.; Cheng, G.; Wen, X.; Liu, Y.; Niu, S.; Wang, Z. L. (ACS Nano, 2014)

(untitled) - Kenry; Yeo, J. C.; Lim, C. T. (Microsyst. Nanoeng., 2016)

(untitled) - Araci, I. E.; Su, B.; Quake, S. R.; Mandel, Y. (Nat. Med., 2014)

(untitled) - Harris, K. D.; Elias, A. L.; Chung, H.-J. (J. Mater. Sci., 2016)

(untitled) - Xiang, Z.; Yen, S.-C.; Sheshadri, S.; Wang, J.; Lee, S.; Liu, Y.-H.; Liao, L.-D.; Thakor, N. V.; Lee, C. (Adv. Mater. (Weinheim, Ger.), 2016)

(untitled) - Lee, C.; Kim, M.; Kim, Y. J.; Hong, N.; Ryu, S.; Kim, H. J.; Kim, S. (Int. J. Control, Autom. Syst., 2017)

(untitled) - Wang, M.; Zhang, J.; Tang, Y.; Li, J.; Zhang, B.; Liang, E.; Mao, Y.; Wang, X. (ACS Nano, 2018)

(untitled) - Wang, M.; Zhang, N.; Tang, Y.; Zhang, H.; Ning, C.; Tian, L.; Li, W.; Zhang, J.; Mao, Y.; Liang, E. (J. Mater. Chem. A, 2017)

(untitled) - Luo, J.; Wang, Z.; Xu, L.; Wang, A. C.; Han, K.; Jiang, T.; Lai, Q.; Bai, Y.; Tang, W.; Fan, F. R.; Wang, Z. L. (Nat. Commun., 2019)

(untitled) - Wang, Z. L.; Chen, J.; Lin, L. (Energy Environ. Sci., 2015)

(untitled) - Lin, H.; He, M.; Jing, Q.; Yang, W.; Wang, S.; Liu, Y.; Zhang, Y.; Li, J.; Li, N.; Ma, Y.; Wang, L.; Xie, Y. (Nano Energy, 2019)

(untitled) - Lin, Z.-H.; Cheng, G.; Wu, W.; Pradel, K. C.; Wang, Z. L. (ACS Nano, 2014)

(untitled) - Parida, K.; Bhavanasi, V.; Kumar, V.; Bendi, R.; Lee, P. S. (Nano Res., 2017)

(untitled) - Mao, Y.; Zhang, N.; Tang, Y.; Wang, M.; Chao, M.; Liang, E. (Nanoscale, 2017)

(untitled) - Wang, Z.; Liu, W.; He, W.; Guo, H.; Long, L.; Xi, Y.; Wang, X.; Liu, A.; Hu, C. (Joule, 2021)

(untitled) - Li, Z.; Chen, J.; Yang, J.; Su, Y.; Fan, X.; Wu, Y.; Yu, C.; Wang, Z. L. (Energy Environ. Sci., 2015)

(untitled) - Wang, Z. L.; Song, J. (Science, 2006)

(untitled) - Ning, C.; Tian, L.; Zhao, X.; Xiang, S.; Tang, Y.; Liang, E.; Mao, Y. (J. Mater. Chem. A, 2018)

(untitled) - Ding, W.; Wang, A. C.; Wu, C.; Guo, H.; Wang, Z. L. (Adv. Mater. Technol. (Weinheim, Ger.), 2019)

(untitled) - Tang, Y.; Zhou, H.; Sun, X.; Diao, N.; Wang, J.; Zhang, B.; Qin, C.; Liang, E.; Mao, Y. (Adv. Funct. Mater., 2020)

(untitled) - Fan, F.-R.; Tian, Z.-Q.; Wang, Z. L. (Nano Energy, 2012)

(untitled) - Niu, S.; Wang, Z. L. (Nano Energy, 2015)

Triboelectric Nanogenerators - Wang, Z. L.; Lin, L.; Chen, J.; Niu, S.; Zi, Y. (Springer International Publishing, 2016)

(untitled) - Jiang, T.; Chen, X.; Yang, K.; Han, C.; Tang, W.; Wang, Z. L. (Nano Res., 2016)

(untitled) - Cheng, G.-G.; Jiang, S.-Y.; Li, K.; Zhang, Z.-Q.; Wang, Y.; Yuan, N.-Y.; Ding, J.-N.; Zhang, W. (Appl. Surf. Sci., 2017)

(untitled) - Chung, J.; Lee, S.; Yong, H.; Moon, H.; Choi, D.; Lee, S. (Nano Energy, 2016)

(untitled) - Yang, W.; Wang, X.; Li, H.; Wu, J.; Hu, Y. (Nano Energy, 2018)

(untitled) - Seol, M.-L.; Han, J.-W.; Moon, D.-I.; Yoon, K. J.; Hwang, C. S.; Meyyappan, M. (Nano Energy, 2018)

(untitled) - Jing, Q.; Zhu, G.; Bai, P.; Xie, Y.; Chen, J.; Han, R. P. S.; Wang, Z. L. (ACS Nano, 2014)

(untitled) - Gogurla, N.; Roy, B.; Park, J.-Y.; Kim, S. (Nano Energy, 2019)

(untitled) - Zhang, B.; Tang, Y.; Dai, R.; Wang, H.; Sun, X.; Qin, C.; Pan, Z.; Liang, E.; Mao, Y. (Nano Energy, 2019)

(untitled) - Mao, Y.; Geng, D.; Liang, E.; Wang, X. (Nano Energy, 2015)

(untitled) - Paosangthong, W.; Wagih, M.; Torah, R.; Beeby, S. (Nano Energy, 2019)

(untitled) - Willatzen, M.; Wang, Z. L. (Nano Energy, 2018)

(untitled) - Lin, S.; Xu, C.; Xu, L.; Wang, Z. L. (Adv. Funct. Mater., 2020)

(untitled) - Wang, Z. L.; Wang, A. C. (Mater. Today, 2019)

(untitled) - McCarty, L. S.; Whitesides, G. M. (Angew. Chem., Int. Ed., 2008)

(untitled) - Baytekin, H. T.; Patashinski, A. Z.; Branicki, M.; Baytekin, B.; Soh, S.; Grzybowski, B. A. (Science, 2011)